Erotic Exuberance: Bataille’s Notion of Eroticism - THOMAS MINGUY (PhaenEx: Journal of Existential and Phenomenological Theory and Culture, 2017)
The figure of Eros is permeated with a logic of lack and fulfillment. As a figure of desire that seeks to be filled, that craves the ineffable, Eros is appropriately described by Plato as the child of poverty and abundance. It is a form of desire that seeks to take what lies outside, to possess the unpossessed and to devour what is desirable. Is it possible, however, to conceive of Eros—and eroticism—as something that is not working according to the traditional logic of desire? Such seems to be the task of Georges Bataille’s philosophy. Refusing the vision of Eros as a quest for pleasure, he developed a thought of eroticism as sovereignty through evil. This article aims at exploring what this evil entails; what a transgression of moral norms, seriousness, and selfhood means. Bataille is famously considered to be a thinker fascinated by evil, and it seems that such a consideration is too easily a reason to avoid him. I would like to show that his thoughts concern freedom, sovereignty and community. Through erotic transgressions, Bataille saw the possibility for true human freedom and communication. Evil as liberation and not Eros as pleasure. I take on a new approach regarding Eros through an exploration of Bataille’s notions of continuity, morality, transgression, death and holiness. The first part of the article will set down the basis of Bataille’s thought. The second will deal in detail with transgression and death, and finally I will deal with holiness, thus making the final step on the path to sovereignty.